2018
DOI: 10.1155/2018/3465897
|View full text |Cite
|
Sign up to set email alerts
|

Acupoint Embedding of Polyglactin 910 Sutures in Patients with Chronic Pain due to Cervical Spondylotic Radiculopathy: A Multicenter, Randomized, Controlled Clinical Trial

Abstract: Objective We aimed to investigate the effectiveness of acupoint polyglactin 910 (PGLA) embedding in patients with cervical spondylotic radiculopathy (CSR). Methods A total of 102 CSR patients with neck and shoulder pain were recruited and assigned randomly into three groups: the sham acupoint embedding (SAE) group, the middle-layer acupoint PGLA embedding (MAPE) group, and the deep-layer acupoint PGLA embedding (DAPE) group. The primary outcomes were Visual Analog Scale (VAS) scores showing the analgesic effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(47 citation statements)
references
References 17 publications
1
46
0
Order By: Relevance
“…25 Several studies have been conducted to prove the safety and effectiveness of TEA. Kim et al 15 and Chu et al 16 conducted RCTs and reported that TEA was not associated with serious side effects of TEA and that it significantly improved the quality of life of patients. Kim et al 26 reported that there was a significant improvement of pain relief in TEA compared to that with conventional physical therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 Several studies have been conducted to prove the safety and effectiveness of TEA. Kim et al 15 and Chu et al 16 conducted RCTs and reported that TEA was not associated with serious side effects of TEA and that it significantly improved the quality of life of patients. Kim et al 26 reported that there was a significant improvement of pain relief in TEA compared to that with conventional physical therapy.…”
Section: Discussionmentioning
confidence: 99%
“…13 In a rat model, TEA controlled the activation of the GluN1 subunit of the NMDA receptor and blocked the Ca ++dependent channels involved in inflammatory pain reaction. 14 Although several randomized control trials (RCTs) have shown that TEA has a more effective and longlasting therapeutic potential than sham thread, conventional analgesics, or other treatments, 15,16 there is limited evidence on the therapeutic effect of TEA in NPNP. 8 Therefore, this study aims to evaluate the effectiveness of TEA compared to that of other treatment methods in the treatment of NPNP.…”
Section: Introductionmentioning
confidence: 99%
“…None of the studies differed significantly regarding general information such as sex ratio, age, and morbidity period between groups before treatment. Three studies experienced dropouts [14,21,30]. Thirty-five dropout cases were reported overall, including 21 in treatment groups and 14 in control groups.…”
Section: Basic Characteristics Of the Studiesmentioning
confidence: 99%
“…Thirty-five dropout cases were reported overall, including 21 in treatment groups and 14 in control groups. All trials were conducted in China of which, one study was written in English [14]. Four studies involved three-arm parallel trials [14,17,21,33], and the remainder all involved two-arm trials.…”
Section: Basic Characteristics Of the Studiesmentioning
confidence: 99%
“…Yasuhisa Tanaka 20 Score Scale The Yasuhisa Tanaka 20 Score Scale [14][15][16] has proven its efficiency to assess cervical spondylotic radiculopathy. It consists of nine items, which includes the severity of neck pain, stupefaction, and the pain from upper limbs or fingers.…”
Section: Primary Outcome Measurementmentioning
confidence: 99%